Coaching in the System of Professional Training of Future Masters of Primary Education During the Period Under Martial Law - Tsiuniak, Oksana; Kopchuk-Kashetska, Mariia; Dovbenko, Svitlana (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
This article highlights the relevance of the problem of using coaching in the professional training of future masters of primary education under martial law. Theoretical analysis of scientific sources on comprehension of the definitions of "coaching" and "pedagogical coaching" is carried out; the essence, purpose, and tasks are revealed. It is noted that the purpose of pedagogical coaching is to reveal the potential for improvement of the expected learning outcomes, development of critical and logical thinking, formation of mobility, independence in decision-making, the desire for self-development, self-learning, and success in future professional activities among higher education students. It has been found that the introduction of coaching in the system of professional training of future masters of primary education will serve the process of training competitive and competent specialists with formed values, beliefs, and priority goals. They are capable of making both personal and professional independent decisions and generating new ideas. This method also helps master's students to develop appropriate self-esteem and academic stress resistance. This is the basis of educational and cognitive activity in the conditions of wartime. It is concluded that coaching belongs to innovative technologies of professional education; it is a powerful tool for personal and professional growth for future masters of primary education; it is a technology for organizing scientific and pedagogical research that promotes the implementation of a student-centered approach in higher education institutions based on trust, partnership, and mutual respect. It is also important to provide a comprehensive rather than fragmentary implementation of coaching to achieve the aims of professional education, improve its quality, and establish cooperative subject-subject relations between professors and students.